2002
DOI: 10.1097/00004872-200210000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal nitric oxide synthase and renin stimulation by sodium deprivation are dependent on the renal nerves

Abstract: The renal nerves mediate the increase of renin and nNOS mRNA during sodium restriction, while the suppression of nNOS and renin gene expression during a sodium load is independent of the presence of the renal nerves. The parallel changes in renin and nNOS mRNA during different sodium intakes suggest that nNOS can be part of the complex, and still largely unclarified, macula densa mechanism of renin regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…However, it is well known that renal sympathetic tone regulates renin release from the juxtaglomerular apparatus. This finding is consistent with those of previous studies, which demonstrated that plasma renin activity is not affected in high-salt–fed SHR following renal denervation (43, 44). Thus, the contribution of the sympathetic nervous system on renin release may be reduced on a high-salt diet.…”
Section: Discussionsupporting
confidence: 94%
“…However, it is well known that renal sympathetic tone regulates renin release from the juxtaglomerular apparatus. This finding is consistent with those of previous studies, which demonstrated that plasma renin activity is not affected in high-salt–fed SHR following renal denervation (43, 44). Thus, the contribution of the sympathetic nervous system on renin release may be reduced on a high-salt diet.…”
Section: Discussionsupporting
confidence: 94%
“…During a low-sodium diet, the nNOS mRNA expression is upregulated in the renal cortex. 16,17 NO from the MD could then diffuse into the JG cells and increase renin exocytosis through cGMP-mediated inhibition of PDE3, as suggested by Reid in 1994. 18 In the present study, this hypothesis is supported by the increased sensitivity to PDE3 inhibition in the nNOS −/− , which suggests that the PDE3 isoform in the JG cells is less inhibited due to the absence of nNOS-derived NO.…”
Section: Discussionsupporting
confidence: 70%
“…16,17 During higher sodium loads, the differences in milrinone response between the genotypes would be expected to be lower, given the reduced nNOS expression.…”
Section: Discussionmentioning
confidence: 99%
“…A general stimulatory role of renal sympathetic nerve activity has been shown by pharmacological blockade of ß1-receptors, renal denervation, and genetic deletion of both ß1-and ß2-receptors (ß1/ß2 double knockout mice), which all significantly reduced the renin synthesis and/or plasma renin levels under control conditions [18,26,37,50,58,82]. In some but not all studies, renal denervation or ß-receptor blockade affected the saltdependent regulation of the renin system such that the absolute levels of renal renin mRNA expression and plasma renin activity were lower under low or high salt load compared with those in the animals or humans with intact renal efferent inputs [47,49,53,82,96,119]. Notably, the salt-dependent regulation of the renin system was not abrogated in any of these studies, and the relative stimulation of the renin system, which was calculated as the stimulation relative to baseline values under normal salt intake, was maintained in the absence of renal ß-adrenergic innervation [82].…”
Section: Renal Sympathetic Nerve Activitymentioning
confidence: 99%